Real-world FDA database analysis unveiling cardiovascular adverse events associated with bispecific T cell engagers in multip myeloma - Chang Shan; Yanli Zhang; Xinxin Zhang; Lu Li; Yanwei Chen; Ying Liu (Scientific Reports)
Abstract Our study aimed to analyze the reported cardiovascular AEs (CVAEs) associated with approved bispecific T-cell engagers (BiTEs) for multiple myeloma (MM), providing insights that could guide safer clinical use of BiTEs. Data were obtained from the FDA Adverse Event Reporting System (FAERS) database for the period from the fourth quarter of 2022 to the first quarter of 2024. A total of 1336 adverse events were reported, of which 112 were CVAEs, accounting for 8.4%. Reporting odds ratio (ROR) and information components (ICs) were extracted from the disproportionality analysis. At standardized MedDRA querie (SMQ) level, arrhythmias (n = 41, ROR025 = 1.49), noninfectious myocarditis/pericarditis (n = 184, ROR025 = 3.11), cardiomyopathy (n = 33, ROR025 = 1.52), shock (n = 23, ROR025 = 4.13) and cardiac failure (n = 16, ROR025 = 1.17) exhibited the positive signal strengths in ROR. And logistic regression analysis reveals that critical risk factors for BiTE-associated CVAEs include older age, male sex, weight loss, cytokine release syndrome, and respiratory failure. In the time-to-onset analysis, majority of CVAEs occurred within the first month (60.9%) and had early-failure type characteristics. It also should be emphasized that CVAEs were commonly associated with serious outcomes, with the most frequently reported being death (34%) Findings above suggest BiTE therapy in MM patients is significantly associated with an increased risk of CVAEs in clinic, and those who develop CVAEs have poorer prognosis. The study may provide important evidence for the precise management and mitigation of cardiovascular risks during BiTE therapy in MM patients, ensuring better clinical outcomes.